Типова модель публічного управління розвитком регіонального соціального кластеру - Литвинов, Андрій Олексійович (Національний технічний університет "Харківський політехнічний інститут", 2024)
У статті розроблено та теоретично обґрунтовано типову модель публічного управління розвитком регіонального соціального кластеру. Визначено та охарактеризовано учасників кластеру, відповідно до чотирьох секторів моделі: 1) ядро кластера та постачальники послуг; 2) суб’єкти, які підтримують функціонування й розвиток кластеру; 3) сектор забезпечення; 4) споживачі соціальних послуг. Зазначено, що всі учасники об’єднані єдиними цілями, процесами, відносинами, зв’язками, результатами та методами управління. Визначено, що переваги запропонованої моделі полягають у чіткому розподілені учасників кластерного утворення по секторам і видам діяльності. Типова модель може слугувати теоретико-методичною основою для формування національної бази даних про соціальні кластери як необхідного засобу для збирання й впорядкування інформації про розвиток соціальних кластерів у державі.

The article develops and theoretically substantiates a typical model of public management for the development of a regional social cluster. The participants of the cluster are identified and characterized according to four sectors of the model: 1) the cluster core and service providers; 2) entities supporting the cluster’s functioning and development; 3) the provisioning sector; and 4) social service consumers. It is noted that all participants are united by common goals, processes, relationships, connections, outcomes, and management methods. The main ideas of the regional social cluster are to improve the quality of life for the regional population. The proposed model’s advantages lie in the clear distribution of cluster formation participants by sectors and types of activities. The typical model of public management for the development of a regional social cluster can serve as a theoretical and methodological basis for forming a national database on social clusters, which is essential for collecting and organizing information on social cluster development within the country.
Typical model of public management for the regional social cluster's development
Keywords: публічне управління; децентралізація; кластеризація; інноваційний розвиток; соціальний кластер; регіон; public adminastration; decentralization; clustering; innovative development; social cluster; region